2012
DOI: 10.1007/s11676-012-0241-9
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal associations in different forest tree species of Hazarikhil forest of Chittagong, Bangladesh

Abstract: Biodiversity of arbuscular mycorrhizal (AM) colonization and AM fungal spores were studied in the roots and rhizosphere soils of Acacia catechu (L.f). Wild., A. mangium Willd, Anthocephala cadamba Miq., Artocarpus chaplasha Roxb., Chickrassia tabularis A. Juss., Swietenia macrophylla King., Tectona grandis L. from plantations; Albizia procera (Roxb.) Benth., A. falcataria L., Alstonia scholaris (L.) R. Br., Aphanamixis polystachya (Wall.) Parker., Hydnocarpus kurzii (King.) Warb., Heynea trijuga Roxb., Lagerst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
(51 reference statements)
1
10
1
Order By: Relevance
“…The results of the present study showed that the eight tree species examined in the planted forest were colonized by AMF. However, the AMF colonization status varied significantly depending on sampling point and the planted tree species, consistent with the results of a previous study on AMF of tree species in different forests [22]. Similar variations in AMF colonization have also been found in other types of forests, such as tropical rainforests [24,49] and peat swamp forests [50].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of the present study showed that the eight tree species examined in the planted forest were colonized by AMF. However, the AMF colonization status varied significantly depending on sampling point and the planted tree species, consistent with the results of a previous study on AMF of tree species in different forests [22]. Similar variations in AMF colonization have also been found in other types of forests, such as tropical rainforests [24,49] and peat swamp forests [50].…”
Section: Discussionsupporting
confidence: 89%
“…The biological and functional diversity of AMF is vitally important to forest ecosystems, and can be decisive for plant community structures and productivity [14,15]. Previous studies on AMF diversity in forests have been conducted mainly in Brazil [16,17], Mexico [18], USA [19], India [20,21], Bangladesh [22], Ethiopia [23], and China [24]. In China, AMF diversity was examined in grassland ecosystems [25,26], an agroecosystem [27], a wetland ecosystem [28], and a natural forest ecosystem [29], mostly concentrating on medicinal plants [30,31] and herbaceous plants [32].…”
Section: Introductionmentioning
confidence: 99%
“…Our results therefore suggest that in order to have a more complete picture of the AMF communities associated with tropical trees, it is important to use both methodologies, collection of AMF from rizosphere soil and cultivation using trapplants. Dhar and Mridha (2012) showed colonization percentages for hyphae and vesicles of 60 and 40%, respectively, and the percentage of arbuscules of 19% for mahogany plantations in Bangladesh. A lower potential Total colonization 53.3 ± 2.01a 41.5 ± 2.01b 51.4 ± 0.03a 40.6 ± 0.03b % Arbuscules 26.3 ± 1.88a 17.6 ± 1.88b 24.6 ± 0.06a 14.1 ± 0.06b % Vesicles 11.3 ± 1.01a 13.23 ± 1.01a 10.6 ± 0.02a 11.8 ± 0.02a % Hyphae 26.5 ± 1.40a 14.6 ± 1.40b 22.6 ± 0.02a 14.21 ± 0.02b % Endophytes 6.09 ± 0.93a 5.5 ± 0.93a 5.2 ± 0.05a 4.12 ± 0.05a…”
Section: Discussionmentioning
confidence: 97%
“…Percent root colonization was calculated. 17 Percent root colonization was determined using the following formula:…”
Section: Amf Assessmentmentioning
confidence: 99%